THE RELATIONSHIP BETWEEN SOCIAL INTERACTION AND THE QUALITY OF LIFE OF FAMILIES WITH A MEMBER WITH MENTAL DISORDERS - Endah Sri Wijayanti; Dhiva Damayanti; Iswatun Iswatun; Joko Susanto; Khotibul Umam (Journal of Vocational Nursing, 2026)
Introduction: Each family has different patterns of social interaction and quality of life depending on the family’s ability to solve problems. Social interaction is the foundation of social and human life and is important for the development of individuals and society as a whole. This study aims to determine the relationship between social interaction and the quality of life of families with members experiencing mental disorders at the UPT Tikung Lamongan Health Center. Methods: This study used an analytical cross-sectional approach. The population consisted of all families with members experiencing mental disorders recorded in the UPT Tikung Lamongan Health Center register, totaling 90 people. The sampling technique used was purposive sampling. Based on the inclusion and exclusion criteria, 85 respondents were obtained. The instruments used in this study were a social interaction questionnaire and the World Health Organization Quality of Life-BREF (WHOQOL-BREF) questionnaire. Data were analyzed using the Spearman rank statistical test. Results: The results showed that 10 respondents (11.8%) had poor social interaction, 20 respondents (23.5%) had moderate social interaction, and 55 respondents (64.7%) had good social interaction. Most respondents had a good quality of life, namely 75 respondents (88.2%), while 10 respondents (11.8%) had a moderate quality of life. Conclusions: The study concluded that families of people with mental disorders in the UPT Puskesmas Tikung Lamongan area generally had good social interaction and quality of life in dealing with mental disorders. Families are expected to maintain a good quality of life and continue providing support and motivation to people with mental disorders to undergo regular treatment.